Possible reason increase of jellyfish population in the Sea of Azov - Minchenko, O. V. (ТДАТУ, 2021)
Іt is worth to noting that since the increase in the sea salinity is directly dependent on rising air temperatures, probably the global trend of rising temperatures makes itself felt, precisely on the example of the Sea of Azov.
Keywords: number of jellyfish; Rhizostoma pulmo; Aurelia aurita; human health